Unambiguous typing of canine adenovirus isolates by deoxyribonucleic acid restriction-endonuclease analysis. - Assaf, R (1983)
Viral deoxyribonucleic acid extracted from a limited number of cells infected with canine adenovirus type 1 or type 2 was cleaved with several restriction endonucleases. Agarose gel electrophoresis of the limit digests showed stable differences between the canine adenovirus type 1 and type 2 cleavage patterns. Rapid and accurate typing of large numbers of clinical isolates may thus be done by deoxyribonucleic acid restriction-endonuclease analysis.